Study on suitable conditions for obtaining zinc – enriched yeast biomass by strain Saccharomyces pastorianus strain CNTP 4054 - Hong Quang, Le; Thi Trang, Nguyen; Duc Manh, Le; Thi Minh Khanh, Nguyen; Thanh Ha, Trinh; Thi Tham, Le; Thu Trang, Pham (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 2S, 2017)
Yeast has long been considered to be one of the main subjects of the food industry. Yeast has the ability to absorb and assimilate zinc to creating a group of zinc – enriched yeast products, which are source of functional products with high nutritional value, ensuring food safety. In this study, we examined, selected some conditions that affected the uptake of zinc – enriched yeast biomass by Saccharomyces pastorianus CNTP 4054 with high level of zinc accumulation. This strain was from strains collection in the Center of Industrial Microbiology, in Food Industries Research Institute. Suitable fermentation conditions for zinc – enrich biomass by strain Saccharomyces pastorianus CNTP 4054 were glucose – 200g/L, yeast extract – 50g/L, ZnSO4 – 750mg/L, fermented at 30°C for 72 Hour, input value pH = 7.